Whole-cycle analysis of echocardiographic tissue Doppler velocities as a marker of biological age - Wang, Joanna Nan; Olsen, Niels Thue; Taraldsen, Ida Arentz; Mogelvang, Rasmus (Frontiers in Cardiovascular Medicine, 2023)
Purpose Tissue Doppler imaging (TDI) is a sensitive marker of impaired cardiac function and different phases of the TDI curve carry different prognostic information. It is not known how continuous TDI curves change with age in normal subjects, and whether these changes differ from changes seen in individuals at risk of future cardiac events. Methods A total of 1,763 individuals from the general population were examined with color TDI at the septal and lateral mitral sites. A low-risk group was defined as without cardiac risk factors (hypertension, diabetes or ischemic heart disease) at baseline and without any cardiac events (cardiovascular death or admission due to either heart failure or acute myocardial infarction) during 10-years follow-up. All TDI curves were corrected for heart rate, and whole-cycle analysis of age-related changes to TDI velocities was performed in both low-risk (n = 881) and high-risk individuals (n = 882). Results In the low-risk population, four phases where myocardial velocity differed most (p < 10–10) according to age were identified [in a standardized cardiac cycle of 1 second (s)]: Systolic peak (0.09–0.13 s), systolic plateau (0.18–0.27 s), early diastole (0.43–0.54 s) and late diastole (0.88–0.95 s). With increasing age, systolic velocities decreased, early diastolic velocities decreased and had delayed peak, and late diastolic velocities increased until age 70 and then stopped increasing. In the high-risk population, comparison to corresponding age groups of the low-risk population showed: Lower early diastolic velocities in 20–40-year-olds; higher late diastolic velocities and lower peak systolic velocities in 40–60-year-olds; further decreased systolic velocities including the systolic plateau and decreased late diastolic velocities in 60-year-olds. The time segments around the systolic peak (p = 0.002) and early diastole (p < 0.001) differed significantly between the high-risk and low-risk population, thus making it possible to use the individual age gap between a TDI-derived biological age and the real chronological age as a tool to discriminate high-risk individuals from low-risk individuals. Conclusion We found that individuals with cardiac risk factors display findings compatible with an accelerated aging of the heart and thus propose TDI-derived biological age as a tool to identify high-risk patients.